Integrated Plasma Metabolomics and Gut Microbiota Analysis: The Intervention Effect of Jiawei Xiaoyao San on Liver Depression and Spleen Deficiency Liver Cancer Rats - Li, Zhuoxian; Zhao, Youxing; Cheng, Jinlai; Xu, Lijing; Wen, Xiaoyu; Sun, Yuhao; Xia, Meng; He, Yining (Frontiers in Pharmacology, 2022)
Primary liver cancer is one of the most common malignant tumors, the hepatocellular carcinoma (HCC) is the most common type of cancer of the liver, occupy the 75% - 85% of primary liver cancer, has a high mortality rate, current study has found that is common in patients with liver cancer with intestinal flora and the condition of metabolic disorders, Chinese herbal medicine is closely related to the composition of intestinal microorganisms and the transformation of active metabolites. Many scholars are trying to develop related drugs to assist the treatment of liver cancer. In the preliminary study of the research group, it was found that the Jiawei Xiaoyao San has a certain therapeutic effect on liver cancer, but the specific mechanism is still unclear. Therefore, this study constructed liver cancer rat model with liver stagnation and spleen deficiency, in order to explore the regulatory effect of Jiawei Xiaoyao San on plasma metabolites and intestinal microflora, and to find the potential mechanism of Jiawei Xiaoyao San in the treatment of liver cancer.Plasma samples and fecal samples were collected from liver cancer rats with liver stagnation and spleen deficiency for microbiome 16S rDNA sequencing and metabolic HPLC-ESI-TOF-MS analysis.Various bioinformatics methods were used to analyze the dataset individually and in combination.The analysis and identification of plasma metabolomics showed that the intervention effect of Jiawei Xiaoyao San on liver cancer rats with liver depression and spleen deficiency was related to 11 differential metabolites and signal pathways such as Primary bile acid biosynthesis, Phenylalanine metabolism, Pantothenate and COA biosynthesis, Metabolic pathways, Cholesterol metabolism and Bile secretion.Combined with fecal microbiological analysis, it was found that Jiawei Xiaoyao San could significantly change the composition of intestinal flora in liver cancer rats, increase beneficial bacteria and reduce the composition of harmful bacteria.This study provides a certain basis to show that the potential mechanism of Jiawei Xiaoyao San in the treatment of liver cancer may play the role of dispersing stagnated liver qi to relieve depression and promoting blood circulation and detoxication by regulating metabolism and intestinal flora, so as to achieve the purpose of curing liver cancer.